Using GIS and Remote Sensing to Study Water Quality Changes and Spectral Analysis for AL-Hawizah Marshes, South of Iraq - Hashesh, Tabarak S.; Ahmed, Bushra A. (Iraqi Journal of Science, 2018)
The aim of this research is to measure the changes of Iraqi Marshland's area as well as the changes in the spectral reflectivity water quality, analyzing seasonal difference in AL-Hawizah marshes, South of Iraq using Geographic Information Systems (GIS) and remote sensing techniques. For this paper, the samples were taken at 10 sites along the study area. Satellite images of the 8 Landsat on 20/5/2017, 8/8/2017, 11/10/2017 and 14/12/2017 have been selected in order to study the seasonal changes on the marshes took place during 2017. The reflectance values of red, green, blue and near infrared bands showed that are significantly associated with a seasonal factor. All bands show that reflectivity of the marsh has been affected by locational variance of reflectance. Also in this paper applying the (Inverse distance weighting) IDW exact interpolation technique depending on the measured data spectral reflectivity water seasonal were distributed on the areas of Iraqi Marshland using Geographic Information System. This technique utilizes for generating thematic map of each seasons to assessment water quality in AL_Hawizah marshes, south of Iraq.